Legal Counseling "Stop Bullying as a Prevention of Student Bullying" at SMAN 1 Cikarang Pusat - Nining Yurista Prawitasari; Akbar Sayudi; Nuraeni (Jurnal Pengabdian Masyarakat Formosa, 2023)
Bullying is a social problem that never ends in society. These problems can be found in various social contexts such as education, the world of work, even in everyday life. Perpetrators and victims also come from various age backgrounds. Children and adolescents are an age that is vulnerable to bullying. Schools are the places most frequently encountered cases of bullying, in fact, sometimes this problem has been internalized with other activities such as the new student orientation period. Bullying behavior in the school environment can create an environment that is less supportive of students' self-development, can hurt students, so they feel unwanted and rejected by their environment. This of course will have an effect on various student activities at school. The causes of bullying are caused by family factors, environmental factors, school factors and social environment factors. Bullies are students who have more physical or social strength than other friends, have a high temperament, and have a low sense of empathy. Victims of bullying who often fight against perpetrators, but some of them obey the perpetrator's orders and don't dare because they are afraid. Therefore, to tackle bullying, every school needs counseling that can increase students' understanding of bullying. The methods used in this extension are (1) lectures; (2) discussion; (3) feedback; and (4) video playback. The results of the counseling show that there is awareness among students that bullying can come in various forms. Students also realize the need for their role in reducing cases of bullying that occur at school.